Mechanism of protective effect of lettuce against glucose/serum deprivation-induced neurotoxicity. (April 2015) - Ghorbani, Ahmad; Sadeghnia, Hamid Reza; Asadpour, Elham
Abstract : Objectives: The present study investigated the protective effect of ethyl acetate fraction of lettuce ( Lactuca sativa ) against glucose/serum deprivation (GSD)-induced neurotoxicity, a model which simulates neuronal damage during ischemia. Methods: Two neuron-like cells, N2a and PC12, were cultivated for 12 hours in GSD condition in the absence or presence of the lettuce fraction. The cell viability, DNA damage, and proapoptotic or antiapoptotic proteins levels were determined using MTT, comet, and immunoblotting assays, respectively. In addition, the intracellular reactive oxygen species and lipid peroxidation levels were measured by fluorimetric methods. Results: In both N2a and PC12 cells, GSD condition significantly decreased the cell viability which was accompanied by increased intracellular reactive oxygen species production, lipid peroxidation level, and oxidative DNA damage. All the GSD-induced neurotoxic changes were inhibited by the lettuce fraction. Lettuce also suppressed the elevated Bax and caspase-3 proteins and decreased Bcl-2 induced by GSD in PC12 cells. Discussion: The present study revealed that lettuce exerts neuroprotective effect through decrease of oxidative stress and inhibition of proapoptotic pathways. Therefore, it has the potential to be used for the management of ischemia-induced neuronal damage.